Digital society and pandemics: An overview - Cyril Modili (Fakultas Ilmu Komunikasi Universitas Mercu Buana, 2023)
Life becomes a new normal during pandemics for everyone. Life becomes increasingly digital as we incorporate them into every aspect of our lives, most notably shopping and education. During this period, technology and pandemic are a natural match. When pandemics strike, information and communication technology add value to society. The term "digital society" refers to a society that makes use of digital technologies on a regular basis (Che Noh et.al., 2017; Hintz, et.al., 2017; Katzenbach and Bachle, 2019). The purpose of this study is to provide an overview of how the digital society functions daily, particularly during pandemics. Additionally, this review article discusses the concepts and characteristics of a digital society, including the usage of digital technology tools, the evolution of tools and digital technology utilised prior to and during pandemics, and the changes in lifestyles in a digital society.